Examining Female Representation in Vascular Physiology: Exercise and hormone effects on arterial morphology and function in females - Thompson, Sarah Louise (Curtin University, 2023)
In vascular physiology, much of what is known about the effects of exercise on arterial structure and function is studied in men. This thesis presents findings from two discrete studies: a systematic review and experimental study. Each study is focussed on female representation both athletic and non-athletic and the effect of exercise on arterial structure and function. An audit framework of best-practice methodologies for studying female populations has been applied to assess study methodological quality.